Study and Evaluation of Release Kinetics of Tramadol HCl from Lipid Based Sustained Release Capsules by Melt Matrix (Dhaka University Journal of Pharmaceutical Sciences, 2013)
The aim of our study was to improve the dissolution of Tramadol hydrochloride (TH) via its semisolid filled lipid based capsules. Sustained release formulation is designed to achieve a prolonged therapeutic effect by continuously releasing medication over an extended period of time after administration of single dose. Semisolid matrixes of TH were prepared by melt-matrix method and were filled in hard gelatin capsule shell (size 0). In this experiment, a mixture of Glycerol monostearate (GMS) and lipid materials like different lipophilic oils and surfactants were used to improve the matrix integrity and drug release. The effects of different oils like Arachis oil, Soyabean oil, castor oil, neobee oil and olive oil and different surfactants such as Span 80, Tween 80, PEG 400, Chremophore RH 40, Cremophor EL were analyzed by formulating at various ratios. The matrices were subjected to the paddle dissolution method using 900 ml of phosphate buffer (pH 6.8). The dissolution test was performed at 100 RPM and the temperature was set at 37 ± 0.50C. The amount of drug was measured from the absorbance with a UV spectrophotometer at 270 nm. The release of drug was plotted in zero order-, 1st order- and Higuchi-release patterns. The correlation coefficients values of the trend lines of the graphs revealed that the formulations best fit in Higuchian release pattern. So it can be said that the pharmaceutical quality of Tramadol HCl capsules can be improved by using a semisolid lipophilic matrix filled in hard gelatin capsules. DOI: http://dx.doi.org/10.3329/dujps.v11i2.14572 Dhaka Univ. J. Pharm. Sci. 11(2): 137-145, 2012 (December)